OPTIMIZATION OF SUPERPLASTICIZED CONCRETE USING TAGUCHI APPROACH: A CASE STUDY OF HYDROPLAST 200 (Nigerian Journal of Technology, 2018)
The use of superplasticizers in concrete using Hydroplast 200 to optimize the contents in a mix proportion was investigated using Taguchi Experimental Design method. Concrete cubes and beams were cast and Taguchi L16 orthogonal array was used to analyze it with five factors namely: water cement ratio, cement content, fine Aggregate content, coarse aggregate content and superplasticizer content. Four levels were selected and the properties varied at these levels. The mixtures were tested both in fresh and hardened states and the best proportions determined. At the minimum level of superplasticizer content, compressive strength of 34.84N/mm2 was achieved and at highest level of superplasticizer considered, compressive strength of 40.5N/mm2 was achieved. The result was in consonance with the predictions of the Taguchi model for optimized superplasticized concrete indicating that at reduced water cement ratio, a 30% increase in compressive strength and 100% increase in flexural strength can be achieved.  http://dx.doi.org/10.4314/njt.v37i3.8